Plasmapheresis in Childhood Guillain-Barre Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The role of plasmapheresis in childhood Guillain-Barre syndrome was examined by retrospective analysis of children admitted to the Children's Hospital of Philadelphia, University of Pennsylvania School of Medicine, Philadelphia, PA.